CONHECIMENTOS LINGÜÍSTICOS EM ENUNCIADOS DE PROVAS DE PORTUGUÊS: DO OBJETO DE REFERÊNCIA CIENTÍFICA AO OBJETO DE ENSINO - Reinaldo, Maria Augusta Macedo (Intercâmbio, 2010)
This study describes the way the multiple-choice questions in the Portuguese exams of the “vestibular” at UFCG are made, and it analyses their legibility to High school teachers and students. The results show that the linguistic terminology is the main factor of illegibility in these exams.